Effects of enzyme preparations on growth performance, meat quality, and hepatic transcriptome of yaks - La, Yongfu; Ma, Xiaoming; Wang, Runli; Mo, Futao; Zhao, Minghui; Yang, Yan; Liu, Xuemei; Wan, Maji; Bao, Pengjia; Chu, Min; Guo, Xian; Yan, Ping; et al. (Frontiers in Veterinary Science, 2026)
The balance between grass and livestock has exacerbated the problem of high-quality development in the yak industry, and the nutritional regulation of enzyme preparations has become a research hotspot. The purpose of this study was to assess and contrast the effects of feeding with various concentrations of enzyme preparations of yaks, including the production performance, meat quality, fatty acid composition of the longissimus dorsi muscle, and gene expression. Adding 0.20% enzyme preparation to the diet can significantly increase the average daily gain (ADG), and reduce the dry matter intake (DMI) and feed conversion rate (FCR), but has no significant effect on the meat quality of yak. In addition, the liver transcriptome and muscle metabolize showed that the addition of enzyme preparations caused differential expression of fatty acid metabolism-related genes in the liver, which may affect the metabolism of fatty acids in the liver and thus alter the fatty acid composition in the longissimus dorsi muscle of yak. The results of this study emphasize that adding enzyme preparations can improve the production performance of yaks without affecting their meat quality, thereby enhancing the economic benefits of yak breeding.